The Salmonella Effector SseK3 Targets Small Rab GTPases - Gan, Jiyao; Scott, Nichollas E.; Newson, Joshua P. M.; Wibawa, Rachelia R.; Wong Fok Lung, Tania; Pollock, Georgina L.; Ng, Garrett Z.; van Driel, Ian; Pearson, Jaclyn S.; Hartland, Elizabeth L.; Giogha, Cristina (Frontiers in Cellular and Infection Microbiology, 2020)
During infection, Salmonella species inject multiple type III secretion system (T3SS) effector proteins into host cells that mediate invasion and subsequent intracellular replication. At early stages of infection, Salmonella exploits key regulators of host intracellular vesicle transport, including the small GTPases Rab5 and Rab7, to subvert host endocytic vesicle trafficking and establish the Salmonella-containing vacuole (SCV). At later stages of intracellular replication, interactions of the SCV with Rab GTPases are less well defined. Here we report that Rab1, Rab5 and Rab11 are modified at later stages of Salmonella infection by SseK3, an arginine N-acetylglucosamine (GlcNAc) transferase effector translocated via the Salmonella pathogenicity island 2 (SPI-2) type III secretion system. SseK3 modified arginines at positions 74, 82 and 111 within Rab1 and this modification occurred independently of Rab1 nucleotide binding. SseK3 exhibited Golgi localization that was independent of its glycosyltransferase activity but Arg-GlcNAc transferase activity was required for inhibition of alkaline phosphatase secretion in transfected cells. While SseK3 had a modest effect on SEAP secretion during infection of HeLa229 cells, inhibition of IL-1 and GM-CSF cytokine secretion was only observed upon over-expression of SseK3 during infection of RAW264.7 cells. Our results suggest that, in addition to targeting death receptor signaling, SseK3 may contribute to Salmonella infection by interfering with the activity of key Rab GTPases.